Islamic Counseling Guidance with Tahajud Prayer Therapy to Reduce Overthinking Habits - Rofi'atin, Alfita Fajar Inayati; Dewi, Riwandah Kusuma; Fadillahwati, Fitria (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
Overthinking is an attitude that usually happens to anyone who is involved in the human thinking process. Without realizing that overthinking will waste our time and energy, people who are always overthinking will find it difficult to take action. Therefore, this can cause a person to fall into anxiety or experience anxiety disorders. Factors from overthinking usually occur because of family problems, relevance, work, studies, and stress. The psychotherapy chosen by the researcher is tahajjud prayer therapy. The selection of the tahajjud prayer is based on the results of previous studies. Judging from the results of previous studies, researchers with knowledge of Islamic psychotherapy are looking for suitable treatment to overcome the problems raised, namely the habit of overthinking in adolescents. Overthinking is overthinking something. People who think too much are more likely to experience constant sadness and negative thoughts, so this also prevents individuals from getting along with themselves. So that researchers can provide solutions in the form of Islamic guidance and counseling through tahajjud prayer therapy. The research method in this study is a literature review sourced from related books and journals.